Improving Editing Efficiency for the Sequences with NGH PAM Using xCas9-Derived Base Editors - Xinyi Liu; Guanglei Li; Xueliang Zhou; Yunbo Qiao; Ruixuan Wang; Shaohui Tang; Jianqiao Liu; Lisheng Wang; Xingxu Huang (Elsevier, 2019)
The development of CRISPR/Cas9-mediated base editors (BEs) provided a versatile tool for precise genome editing. The recently developed xCas9-derived base editors (xBEs) that recognize the NG PAM substantially expand the targeting scope in the genome, while their editing efficiency needs to be improved. Here, we described an improved version of xBEs by fusing the BPNLS and Gam to the N terminus of xBEs (BPNLS-Gam-xBE3 and BPNLS-xABE), and this version of base editor displayed higher targeting efficiency for the majority of detected sites. By using this improved version of xBEs, we successfully created and corrected pathogenic mutations at genomic sites with the NGN protospacer-adjacent motif in human cells. Lastly, we used BPNLS-Gam-xBE3 to model pathogenic mutations in discarded human tripronuclear (3PN) zygotes, and no obvious off-targets and indels were detected. Taken together, the data in our study offer an efficient tool for precise genome editing and, thus, an enriched base editing toolkit. Keywords: CRISPR/Cas, base editor, xCas9, base editing efficiency, pathogenic mutation, Wilson disease